Common Hepatic Duct Mixed Adenoneuroendocrine Carcinoma Masquerading as Cholangiocarcinoma - Sali Priyanka Akhilesh; Yadav Kamal Sunder; Tampi Chandralekha; Parikh Samir; Wagle Prasad Kashinath (Case Reports in Gastrointestinal Medicine)
Bile duct mixed adenoneuroendocrine carcinoma (MANEC) is a rare entity. It is defined as having mixed elements of both neuroendocrine tumors (NET) and an adenocarcinoma element, the lesser component forming at least 30% of the tumor. It is a subtype of neuroendocrine carcinoma (NEC) showing both gland-forming epithelial tumor cells and neuroendocrine cells. It is generally misdiagnosed as cholangiocarcinoma on imaging studies. The preoperative pathological workup from the endoscopic retrograde cholangiography brush cytology usually misses the NET/NEC component since it often lies deeper in the tumor. However, it is reported that it is the NEC component that defines the prognosis of the tumor; hence, it is vital to identify the NEC component. We present a rare case of common hepatic duct (CHD) MANEC that was preoperatively misdiagnosed as cholangiocarcinoma.